1998
DOI: 10.1021/jm970217c
|View full text |Cite
|
Sign up to set email alerts
|

Design of N-Acylprolyltyrosine “Tripeptoid” Analogues of Neurotensin as Potential Atypical Antipsychotic Agents

Abstract: A series of N-acylprolyltyrosine amides was designed as tripeptoid analogues of neurotensin. The substituted dipeptides were tested in vivo for antidopamine activity by their ability to inhibit the apomorphine-induced climbing in mice and the dopamine-induced extrapolatory behavior impairment in rats. The N-acylprolyltyrosine amides structure-activity relationships have indicated the size of the N-acyl group and the configuration of amino acids that are important for the activity. We found that the bioactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…In these compounds, the N-acyl radical simulates the side chain of a third amino acid residue (Leu 13 ), which is remote in the peptide chain but spatially close to Pro 10 [15]. It was found that the introduction of N-acyl radicals in no case decreased, but sometimes increased the activity of obtained compound in the apomorphine-induced verticalization test (Table 4).…”
Section: Design Of the Neurotensinergic Dipeptide Neuroleptic Drug DImentioning
confidence: 99%
See 1 more Smart Citation
“…In these compounds, the N-acyl radical simulates the side chain of a third amino acid residue (Leu 13 ), which is remote in the peptide chain but spatially close to Pro 10 [15]. It was found that the introduction of N-acyl radicals in no case decreased, but sometimes increased the activity of obtained compound in the apomorphine-induced verticalization test (Table 4).…”
Section: Design Of the Neurotensinergic Dipeptide Neuroleptic Drug DImentioning
confidence: 99%
“…N-Caproyl-L-prolyl-L-tyrosine, the most active tripeptoid analog of neurotensin, was used to study the dependence of the neuroleptic activity on the nature of C-substitution [15]. In the series of acid -ester -amide -alkylamide, all compounds were active (Table 5), although the pharmacological activity of acid and substituted amide was less pronounced than of ether and unsubstituted amide.…”
Section: Design Of the Neurotensinergic Dipeptide Neuroleptic Drug DImentioning
confidence: 99%
“…The drug exhibited antipsychotic effects in experiments [2,5]. Because of metabolic instability and low bioavailability of neuropsychotropic drugs of peptidergic structure, it is essential to study their penetration through the blood-brain barrier (BBB) and delivery to the target organ (brain) for realization of their effects in CNS.…”
mentioning
confidence: 99%
“…The dipeptide was identical to the Pro 10 -Tyr 11 fragment of neurotensin. The structure of the peptide analog of sulpiride was modified taking into account the assumption of biological activity for the â-turn conformation of neurotensin, the center of which contains the Pro 10 -Tyr 11 fragment, by adding an N-caproyl radical, which imitates the side radical of Leu 13 in neurotensin that is situated close to the proline [1]. Experiments established the neuroleptic activity of the resulting methyl ester of N-caproyl-L-prolyl-L-tyrosine (dilept) at doses of 0.4 -4.0 mg/kg for i.p.…”
mentioning
confidence: 99%